Intracranial Extension of an Orbital Epidermoid Cyst. Issue 6 (November 2016) - Burnham, Jordan M.; Lewis, Kyle
Abstract : Epidermoid and dermoid cysts represent the most common cystic lesions of the orbit and commonly arise from bony sutures or the intradiplpoic space of orbital bones. Massive intracranial extension of an epidermoid cyst arising from the intradiploic space of an orbital bone is very rarely seen. We present a case of a 55-year-old male who was incidentally found to have massive intracranial extension of an intradiploic epidermoid cyst of the superolateral orbital bone with minimal symptoms. The cyst was completely excised via a pterional craniotomy and lateral orbitotomy by neurosurgery and oculoplastic surgery teams. The patient suffered no complications and is doing very well. Abstract : This case report presents of an orbital epidermoid cyst with massive intracranial extension.